Factors Affecting Customer’s Menu Item Selection in Restaurants (International Journal of Atharva, 2023)
With the intent of investigating the factors that affected restaurant menu item choice, the data collected from 40 respondents from various restaurants, it was expected that most restaurant supervisors knew the inclinations of their clients. This knowledge was utilized to maximize the experience of the customers and, consequently, increase the restaurant's income. The quantitative data was gathered through a questionnaire survey method, encompassing factors such as customers' personal preferences, budget considerations, variety and options, enticing descriptions, and visual appeal, which all played a role in influencing customers' choices. Moreover, social and cultural factors, health and nutritional concerns, recommendations and reviews, and seasonal specials were found to have an impact on customers' choices.